Selected Aspects of Invasive Solidago canadensis with an Emphasis on Its Allelopathic Abilities: A Review. Issue 10 (23rd September 2022) - Zhu, Xunzhi; Li, Weijie; Shao, Hua; Tang, Shijie
Abstract: Solidago canadensis L., native to North America, is now an invasive plant worldwide. Its abundant seeds, rapid vegetative reproduction ability, and allelopathy to other plants are the main reasons for its successful invasion. It has negative impacts on the ecological environment of the invaded area and causes a reduction in local biodiversity and economic losses of agriculture and stock farming. Each part of the plant contains a variety of allelochemicals (terpenoids, phenolics, and flavonoids), including a large number of essential oil components. These allelochemicals can be released in various ways to inhibit the growth of adjacent plants and promote their invasion; they can also affect soil properties and soil microorganisms. This article summarizes the allelopathic effects of S. canadensis on other plant species and the interaction mechanism between it and the ecosystem. Abstract :